Do pneumatic tube transport systems transmit potential pathogens? A hygienic risk assessment in a university hospital. Issue 3 (March 2020) - Khaznadar, L.; Dancer, S.J.; Petersmann, A.; Seifert, U.; Below, H.; Papke, R.; Suchomel, M.; Kohlmann, T.; Kramer, A.
Summary: Background: Prompted by an outbreak of vancomycin-resistant enterococci (VRE) in a medical facility, this study examined a pneumatic tube transport system (PTS) as a potential transmission channel. Method: Samples from the receiving station and entry racks were gathered via smear technique. Sponges used for PTS decontamination were soaked with 0.89% NaCl and transported through the channel. Micro-organisms were recovered from the tubes and cleaning sponges using a wash-away technique. Air sampling was performed at the receiving station in order to detect any airborne contamination. Tubes were artificially inoculated with Escherichia coli K12 NCTC 10538 and Staphylococcus epidermidis DSM 20044 and sent through the PTS to investigate channel contamination. Results: No pathogens were detected in effluent air from the PTS or in tubes during routine operation. Entry racks for the test tubes were contaminated with coagulase-negative staphylococci (CNS), aerobic bacilli, moulds and vancomycin-susceptible Enterococcus faecium . E. coli proved to be unsuitable for detecting bacterial transmission by the PTS due to low persistence, but S. epidermidis was more resilient. After sending contaminated test tubes through the PTS, levels of S. epidermidis only decreased marginally. Subsequently, sponges soaked with disinfectant solution were put through the system and these eliminated S. epidermidis completely from the first attempt. Discussion: Routine hygienic maintenance of the PTS makes pathogen transmission highly unlikely, although entry racks should be disinfected regularly. Any involvement of the PTS in the VRE outbreak at the study institution was unlikely.